Trafficking culture: new directions in researching the global market in illicit antiquities - Mackenzie, Simon (Routledge, Taylor & Francis Group, 2020)
The structure of the global market in illicit antiquities : actors, drivers, mechanisms -- Interfaces and antiquities smuggling chains : blurring on the margins of "source," "transit," "destination market" -- The trade in illicit antiquities as a transnational criminal market -- The destination market -- White collar crime and facilitation of the criminal market by "legitimate" actors -- Autoregulation of the destination market? -- Regulation, self-regulation and ethical consumption markets -- Policy failure, policy future.